Quantification of vertical ground reaction forces of popular bilateral plyometric exercises - Wallace, B. J.; Kernozek, T. W.; White, J. M.; Kline, D. E.; Wright, G. A.; Peng, H. T.; Huang, C. F. (The Journal of Strength and Conditioning Research, 2010)
The purpose of this study was to quantify the vertical ground reaction forces (VGRFs) developed during the performance of popular bilateral plyometric movements. Fourteen power-oriented track and field men of collegiate and national level randomly performed 3 trials of 9 different bilateral plyometric exercises in a single testing session. Three depth drop (DD) and 3 depth jump (DJ) conditions from 30, 60, and 90 cm heights (DD30, DD60, and DD90 and DJ30, DJ60, and DJ90) were tested, in addition to vertical jump (VJ), standing long jump (SLJ), and 2 consecutive jump (2CJ) conditions. Peak impact VGRFs were normalized to body weight. Additionally, all conditions were compared against the VJ in an intensity index. The SLJ condition resulted in a significantly higher peak VGRF than the 2CJ condition (p <= 0.05). 90DD, 90DJ, 60DD, and SLJ had a significantly greater peak VGRF (5.39, 4.93, 4.30, and 4.22 times body weight, respectively) than the VJ condition (3.34 times body weight). The 30DJ condition had an insignificantly smaller peak VGRF (2.78 times body weight) when compared with the VJ. Practitioners may use these findings to more effectively progress athletes in these movements based on their intensities.